A primer on understanding Google Earth Engine APIs - Reis, Rui (2020)
This article is build on the experience of using Google Earth Engine as a development framework for a previous work by the same authors.Being primarily a distributed parallel computing platform, it is designed around a functional language pattern, even though supported on an object model, and a map / reduce distributed workload paradigm.Leveraging the sheer computing power delivered by the Google infrastructure and a multi petabyte remote sensing data repository, GoogleEarth Engine is an efficient development framework that presents itself in two basic flavors: one online integrated development environment which uses the browser Javascript engine; two APIs that can be deployed to a Python or a NodeJS environment.This work emphasizes the comparison between the Javascript browserbased implementation and the Python environment packages.